Ecological rigidity and the hardness of selection in the wild. (6th April 2020) - Start, Denon
Abstract: Hutchinson's ecological theater and evolutionary play is a classical view of evolutionary ecology—ecology provides a template in which evolution occurs. An opposing view is that ecological and evolutionary changes are like two actors on a stage, intertwined by density and frequency dependence. These opposing views correspond to hard and soft selection, respectively. Although often presented as diametrically opposed, both types of selection can occur simultaneously, yet we largely lack knowledge of the relative importance of hard versus soft selection in the wild. I use a dataset of 3000 individual gall makers from 15 wild local populations over 5 years to investigate the hardness of selection. I show that enemy attack consistently favors some gall sizes over others (hard selection) but that these biases can be fine‐tuned by density and frequency dependence (soft selection). As a result, selection is hard and soft in roughly equal measures, but the importance of each type varies as species interactions shift. I conclude that eco‐evolutionary dynamics should occur when a mix of hard and soft selection acts on a population. This work contributes to the rapprochement of disparate views of evolutionary ecology—ecology is neither a rigid theater nor a flexible actor, but instead embodies components of both.